Controlling alkyne reactivity by means of a copper-catalyzed radical reaction system for the synthesis of functionalized quaternary carbons - Hirata, Goki; Yamane, Yu; Tsubaki, Naoya; Hara, Reina; Nishikata, Takashi (Beilstein Journal of Organic Chemistry, 2020)
A terminal alkyne is one of the most useful reactants for the synthesis of alkyne and alkene derivatives. Because an alkyne undergoes addition reaction at a C–C triple bond or cross-coupling at a terminal C–H bond. Combining those reaction patterns could realize a new reaction methodology to synthesize complex molecules including C–C multiple bonds. In this report, we found that the reaction of 3 equivalents of terminal alkyne 1 (aryl substituted alkyne) and an α-bromocarbonyl compound 2 (tertiary alkyl radical precursor) undergoes tandem alkyl radical addition/Sonogashira coupling to produce 1,3-enyne compound 3 possessing a quaternary carbon in the presence of a copper catalyst. Moreover, the reaction of α-bromocarbonyl compound 2 and an alkyne 4 possessing a carboxamide moiety undergoes tandem alkyl radical addition/C–H coupling to produce indolinone derivative 5.
Keywords: copper catalyst; 1,3-enyne; functionalized quaternary carbon; indolinone; tandem alkyl radical addition

Modern Alkyne Chemistry: Catalytic and Atom- Economic Transformations - Trost, B. M.; Li, C.-J. (Wiley-VCH, 2015)

(untitled) - Chinchilla, R.; Nájera, C. (Chem. Rev., 2007)

(untitled) - Sonogashira, K.; Tohda, Y.; Hagihara, N. (Tetrahedron Lett., 1975)

(untitled) - Liu, W.; Li, L.; Li, C.-J. (Nat. Commun., 2015)

(untitled) - Liu, W.; Chen, Z.; Li, L.; Wang, H.; Li, C.-J. (Chem. – Eur. J., 2016)

(untitled) - Beringer, F. M.; Galton, S. A. (J. Org. Chem., 1965)

(untitled) - Ochiai, M.; Kunishima, M.; Nagao, Y.; Fuji, K.; Shiro, M.; Fujita, E. (J. Am. Chem. Soc., 1986)

(untitled) - Bachi, M. D.; Bar-Ner, N.; Crittell, C. M.; Stang, P. J.; Williamson, B. L. (J. Org. Chem., 1991)

(untitled) - Fernández González, D.; Brand, J. P.; Waser, J. (Chem. – Eur. J., 2010)

(untitled) - Brand, J. P.; Waser, J. (Chem. Soc. Rev., 2012)

(untitled) - Dong, W.; Yuan, Y.; Gao, X.; Keranmu, M.; Li, W.; Xie, X.; Zhang, Z. (Org. Lett., 2018)

(untitled) - Gao, Y.; Zhang, P.; Li, G.; Zhao, Y. (J. Org. Chem., 2018)

(untitled) - Liu, B.; Yu, J.-X.; Li, Y.; Li, J.-H.; He, D.-L. (Org. Lett., 2018)

(untitled) - Gao, Y.; Zhang, P.; Ji, Z.; Tang, G.; Zhao, Y. (ACS Catal., 2017)

(untitled) - Che, C.; Huang, Q.; Zheng, H.; Zhu, G. (Chem. Sci., 2016)

(untitled) - Cheung, C. W.; Zhurkin, F. E.; Hu, X. (J. Am. Chem. Soc., 2015)

(untitled) - Nishikata, T.; Noda, Y.; Fujimoto, R.; Sakashita, T. (J. Am. Chem. Soc., 2013)

(untitled) - Nishikata, T.; Ishida, S.; Fujimoto, R. (Angew. Chem., Int. Ed., 2016)

(untitled) - Ishida, S.; Takeuchi, K.; Taniyama, N.; Sunada, Y.; Nishikata, T. (Angew. Chem., Int. Ed., 2017)

(untitled) - Yamane, Y.; Miwa, N.; Nishikata, T. (ACS Catal., 2017)

(untitled) - Nakamura, K.; Nishikata, T. (ACS Catal., 2017)

(untitled) - Che, C.; Zheng, H.; Zhu, G. (Org. Lett., 2015)

(untitled) - Okuro, K.; Furuune, M.; Enna, M.; Miura, M.; Nomura, M. (J. Org. Chem., 1993)

(untitled) - Gujadhur, R. K.; Bates, C. G.; Venkataraman, D. (Org. Lett., 2001)

(untitled) - Thathagar, M. B.; Beckers, J.; Rothenberg, G. (Green Chem., 2004)

(untitled) - Ma, D.; Liu, F. (Chem. Commun., 2004)

(untitled) - Wang, Y. F.; Deng, W.; Liu, L.; Guo, Q. X. (Chin. Chem. Lett., 2005)

(untitled) - Saejueng, P.; Bates, C. G.; Venkataraman, D. (Synthesis, 2005)

(untitled) - Xie, Y.-X.; Deng, C.-L.; Pi, S.-F.; Li, J.-H.; Yin, D.-L. (Chin. J. Chem., 2006)

(untitled) - Li, J.-H.; Li, J.-L.; Wang, D.-P.; Pi, S.-F.; Xie, Y.-X.; Zhang, M.-B.; Hu, X.-C. (J. Org. Chem., 2007)

(untitled) - Tang, B.-X.; Wang, F.; Li, J.-H.; Xie, Y.-X.; Zhang, M.-B. (J. Org. Chem., 2007)

(untitled) - Guan, J. T.; Yu, G.-A.; Chen, L.; Weng, T. Q.; Yuan, J. J.; Liu, S. H. (Appl. Organomet. Chem., 2009)

(untitled) - Stephens, R. D.; Castro, C. E. (J. Org. Chem., 1963)

(untitled) - Tang, S.; Peng, P.; Zhong, P.; Li, J.-H. (J. Org. Chem., 2008)

(untitled) - Jiang, T.-S.; Tang, R.-Y.; Zhang, X.-G.; Li, X.-H.; Li, J.-H. (J. Org. Chem., 2009)

(untitled) - Liu, C.; Liu, D.; Zhang, W.; Zhou, L.; Lei, A. (Org. Lett., 2013)